2007
DOI: 10.1590/s1678-58782007000300011
|View full text |Cite
|
Sign up to set email alerts
|

A generalized gas-liquid two-phase flow analysis for efficient operation of airlift pump

Abstract: Airlift pumps are finding increasing use where pump reliability and low maintenance are required, where corrosive, abrasive, or radioactive fluids must be handled and when a compressor is readily available. The objective of the present study is to evaluate the performance of a pump under predetermined operating conditions and to optimize the related parameters The effects of design parameters viz. mass flow rate of air, immersion ratio, diameter of rising main etc. on the performance of airlift pump are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The figures show that the effectiveness and efficiency increased until an optimum point, and then decreased with the increase in J G,in . The effectiveness and efficiency increased with the increase in the SR, and both are in qualitatively good agreement with those of [18,19,39]. The results obtained mean that under the same of J G,in , the increase in SR increases the amount of water discharged.…”
Section: The Effectiveness and Efficiency Of The Bubble-generator-type Airlift Pumpsupporting
confidence: 80%
See 1 more Smart Citation
“…The figures show that the effectiveness and efficiency increased until an optimum point, and then decreased with the increase in J G,in . The effectiveness and efficiency increased with the increase in the SR, and both are in qualitatively good agreement with those of [18,19,39]. The results obtained mean that under the same of J G,in , the increase in SR increases the amount of water discharged.…”
Section: The Effectiveness and Efficiency Of The Bubble-generator-type Airlift Pumpsupporting
confidence: 80%
“…Therefore, it is very important to investigate the slug flow characteristics of the airlift pump. Most of the researchers measure slug flow hydrodynamic parameters such as phase velocity, slug length, and void fraction [16,19,39,40]. Hout et al [40] was measuring the slug velocity in stagnant water and it found that the vortex in the liquid slug affects the shape of the trailing bubble.…”
mentioning
confidence: 99%
“…The reported results showed that the water output within the tapered riser pipe is highly sensitive to the airflow rate than the straight riser pipes. In addition to the geometrical parameters, the influence of the operational parameters such as the submergence ratio and the injected fluid flow rate on the liquid flow rate, efficiency, and void fraction were investigated by [12], [13] and [14]. It was concluded that the capacity and efficiency of airlift pumps are a function of submergence ratio and airflow rates.…”
Section: Introductionmentioning
confidence: 99%
“…The flow pattern of the airlift pump was analyzed and discussed by [13], [14], [19] and [20]. It was reported that the main parameters affecting the performance of the airlift pump are the flow pattern inside the riser pipe.…”
Section: Introductionmentioning
confidence: 99%
“…Awari et al [16] tried to evaluate the performance of a pump under predetermined operating conditions and to optimize the related parameters. They presented the effects of design parameters versus mass flow rate of air, immersion ratio, etc.…”
Section: Introductionmentioning
confidence: 99%